Feeding in Domestic Vertebrates: From Structure to Behaviour 2006
DOI: 10.1079/9781845930639.0241
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and mastication behaviour in ruminants.

Abstract: This chapter reviews the specificities of feeding behaviour and mastication in ruminants and their implications for mastication measurement and analysis. The functional role of mastication during eating and ruminating are then discussed, highlighting its major contribution to digestion and the control of intake. The last part of this chapter discusses the variations of rhythm and duration of mastication activities in relation to feed and dietary characteristics on one hand and to animal and group characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Sheep ate for longer when grass hay was orally consumed, whereas they ate faster when it was lucerne hay. This could be explained by the physical differences between lucerne and grass hays: lucerne hay is less fibrous than grass hay, favouring easier prehension and mastication by sheep Baumont et al, 2006) and allows more flexibility in intake rate compared with coarse hays that need intense mastication activity.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep ate for longer when grass hay was orally consumed, whereas they ate faster when it was lucerne hay. This could be explained by the physical differences between lucerne and grass hays: lucerne hay is less fibrous than grass hay, favouring easier prehension and mastication by sheep Baumont et al, 2006) and allows more flexibility in intake rate compared with coarse hays that need intense mastication activity.…”
Section: Discussionmentioning
confidence: 99%
“…Once during the pre-experimental period (Week 6) and four times during finishing (Weeks 4, 8 and 14 for the three diets and Week 19, 22 or 24, respectively, for strawconcentrate, maize silage-concentrate and hay-concentrate diets), the daily eating time of each bull was estimated over the 7 days of the week as the mean daily time during which its feeding gate was open. According to Metz (1975) and Baumont et al (2006), we considered that inter-meal intervals lasted at least 4 min. This feeding behaviour estimation did not include straw ingestion.…”
Section: Measurementsmentioning
confidence: 99%
“…An experiment with Limousin bulls fed a 45% maize silage diet suggests that bulls regulate their intake activity to achieve a balanced intake in terms of concentrate and longfibre roughage to meet their behavioural and physiological requirements (Cozzi and Gottardo, 2005). Mastication activity is a necessity for ruminants and is a component of animal behaviour that has to be taken into account to ensure their welfare (Baumont et al, 2006). A minimum threshold of 10% long-fibre roughage on a dry matter basis -E-mail: mrichard@clermont.inra.fr for beef cattle diets has been proposed to avoid pathological conditions and poor welfare (EU-SCAHAW, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, Baumont et al (2006) as they mentioned that the ingestive behavior didn't affected by the age of cattle. The obtained results in table (2) showed that the mutual suckling time and frequency between the dairy females according to their age were at highest level at early life of age (three years, 9416.0 ± 60.08 a ) and four years, 223.33±17.27 b ) and gradually were disappeared at seven years of age and the differences were significant.…”
Section: Resultsmentioning
confidence: 99%